Hierarchical QAM a spectrally efficient dc-free modulation scheme. - Mirabbasi, S. (IEEE Communications magazine)
A new spectrally efficient, dc-free modulation scheme called hierarchical quadrature amplitude modulation is proposed. The use of HQAM in high-data-rate digital communication systems opens new possibilities for the practical realization of highly integrated receivers.